Characteristics of lesional and extra-lesional cortical grey matter in relapsing–remitting and secondary progressive multiple sclerosis: A magnetisation transfer and diffusion tensor imaging study. (February 2016) - Yaldizli, Özgür; Pardini, Matteo; Sethi, Varun; Muhlert, Nils; Liu, Zheng; Tozer, Daniel J; Samson, Rebecca S; Wheeler-Kingshott, Claudia AM; Yousry, Tarek A; Miller, David H; Chard, Declan T
Background: In multiple sclerosis (MS), diffusion tensor and magnetisation transfer imaging are both abnormal in lesional and extra-lesional cortical grey matter, but differences between clinical subtypes and associations with clinical outcomes have only been partly assessed. Objective: To compare mean diffusivity, fractional anisotropy and magnetisation transfer ratio (MTR) in cortical grey matter lesions (detected using phase-sensitive inversion recovery (PSIR) imaging) and extra-lesional cortical grey matter, and assess associations with disability in relapse-onset MS. Methods: Seventy-two people with MS (46 relapsing–remitting (RR), 26 secondary progressive (SP)) and 36 healthy controls were included in this study. MTR, mean diffusivity and fractional anisotropy were measured in lesional and extra-lesional cortical grey matter. Results: Mean fractional anisotropy was higher and MTR lower in lesional compared with extra-lesional cortical grey matter. In extra-lesional cortical grey matter mean fractional anisotropy and MTR were lower, and mean diffusivity was higher in the MS group compared with controls. Mean MTR was lower and mean diffusivity was higher in lesional and extra-lesional cortical grey matter in SPMS when compared with RRMS. These differences were independent of disease duration. In multivariate analyses, MTR in extra-lesional more so than lesional cortical grey matter was associated with disability. Conclusion: Magnetic resonance abnormalities in lesional and extra-lesional cortical grey matter are greater in SPMS than RRMS. Changes in extra-lesional compared with lesional cortical grey matter are more consistently associated with disability.